2019
DOI: 10.1111/1756-185x.13702
|View full text |Cite
|
Sign up to set email alerts
|

Circulating interleukin‐6 as a biomarker in a randomized controlled trial of modified‐release prednisone vs immediate‐release prednisolone, in newly diagnosed patients with giant cell arteritis

Abstract: Objectives To measure serial interleukin (IL)‐6 levels in newly diagnosed patients with giant cell arteritis (GCA), treated in a randomized controlled trial of modified‐release prednisone (MR) vs immediate‐release prednisolone (IR) used in a tapering regimen conforming to British Society for Rheumatology GCA guidelines. Methods Patients (n = 12) were randomized into 2 treatment arms (7 MR, 5 IR) and followed over 26 weeks. We measured IL‐6 with additional markers. Results A significantly higher overall mean IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Oral administration of the product at night before sleep is designed to lead to the C max of plasma drug concentration occurring in the night and early morning, when proinflammatory cytokines rise to a peak level. 153,154 Lodotra showed a significantly lower IL-6 level compared with immediate-release prednisolone in a clinical study, 154 and this result indicated the usefulness of this technology for patients. In other clinical studies, low absorption was observed in some subjects, which might have been due to variability in transit of the tablet through the gastrointestinal tract, and drug release in a low absorption gastrointestinal region such as the colon.…”
Section: Molecularmentioning
confidence: 97%
“…Oral administration of the product at night before sleep is designed to lead to the C max of plasma drug concentration occurring in the night and early morning, when proinflammatory cytokines rise to a peak level. 153,154 Lodotra showed a significantly lower IL-6 level compared with immediate-release prednisolone in a clinical study, 154 and this result indicated the usefulness of this technology for patients. In other clinical studies, low absorption was observed in some subjects, which might have been due to variability in transit of the tablet through the gastrointestinal tract, and drug release in a low absorption gastrointestinal region such as the colon.…”
Section: Molecularmentioning
confidence: 97%
“…Two RCTs have demonstrated the efficacy of this modified-release (MR) PDN formulation in managing the signs and symptoms of RA, particularly morning stiffness (MS), achieving superior rates of MS improvement after 3 months compared to immediate-release (IR) PDN taken in the morning (33% reduction in the MR group vs. 0% in the IR arm) [35,36]. This formulation has also shown promising results in managing PMR and may be a potential option for better controlling the inflammatory process also in newly diagnosed patients with GCA [37,38]. Although specific recommendations on the use of MR cortisone have not been formulated, it has been suggested that their utilization might be considered in patients experiencing prolonged fatigue and joint stiffness in the morning [20,39].…”
Section: Chronobiology Of Glucocorticosteroids In Rheumatoid Arthritismentioning
confidence: 99%
“…While some studies have reported promising results with specific markers, their clinical utility remains questionable due to assay variability and lack of validation in large prospective cohorts. Of all markers, IL6 is the best studied and has most consistently been shown to be elevated in active disease 15,16 . Studies to date have not rigorously assessed how the timing of collection in relation to commencement of corticosteroid may affect reproducibility.…”
Section: Introductionmentioning
confidence: 99%